Nurturing human intelligence in the age of AI: rethinking education for the future - Luckin, Rosemary (Development and learning in organizations, 2025)
Purpose The purpose of the article “Nurturing Human Intelligence in the Age of AI: Rethinking Education for the Future” is to explore the profound impact of Artificial Intelligence (AI) on education and to emphasize the need for a fundamental shift in current education systems. The article aims to provide practitioners with actionable insights on how to navigate the rapidly evolving landscape of AI in education while preparing young people for their crucial role as the workforce of tomorrow. It seeks to highlight the potential of AI to revolutionize education while also acknowledging the importance of preserving the unique human touch in the learning process. Design/methodology/approach This article explores the disruptive impact of Artificial Intelligence (AI) on education and emphasizes the need for a fundamental shift in current education systems to prepare young people for an AI-driven future. It highlights the potential of AI to revolutionize education through personalized learning experiences, enhanced teacher professional development and automation of administrative tasks while acknowledging the importance of approaching AI implementation with caution and preserving the unique human touch in education. The article argues for a shift in focus from rote learning to fostering critical thinking, creativity and problem-solving skills, emphasizing the development of Learning Mastery and Knowledge Mastery. It underscores the vital role of educators in leveraging AI technologies and preparing young people for the future, along with the need for responsive educational policies and curriculum frameworks that integrate AI literacy and ethical considerations. The article concludes by calling for reimagining the schooling system, prioritizing high-level thinking and nurturing the unique capabilities of human intelligence. The future of education lies in harnessing the power of AI while celebrating and cultivating distinctively human qualities. Educational practitioners play a crucial role in shaping this future by bridging the gap between research and practice, ensuring a positive and prosperous future for society in an AI-driven world. Findings (1) AI can revolutionize education through personalized learning, enhanced teacher development and task automation. (2) Balance is needed between AI and human touch in education. Current education systems fail to cultivate critical thinking and creativity. (3) Learning Mastery and Knowledge Mastery should be emphasized to foster independent thinking and problem-solving. (4) Educators play a vital role in integrating AI into the learning process. (5). AI can redefine success in education and cultivate future-proof skills. (6). Responsive and adaptable educational policies are necessary. (7) The future of education lies in harnessing AI while nurturing human intelligence. Research limitations/implications Not appropriate for style of text. Practical implications (1) Educators should actively engage with AI technologies and explore ways to integrate them into the learning process to enhance personalized learning experiences. (2) Professional development programs should be designed to equip teachers with the necessary skills to effectively utilize AI tools and leverage them to improve instructional practices. (3) Curriculum frameworks need to be revised to integrate AI literacy, digital citizenship and ethical considerations into the educational journey of young learners. (4) Educational institutions should invest in AI-powered assessment tools that provide a holistic understanding of a student’s abilities, capturing their strengths and areas for improvement beyond test scores. (5) Educators should focus on teaching metacognitive strategies, encouraging self-reflection and self-assessment and providing opportunities for students to develop problem-solving and critical-thinking skills. (6) Active learning strategies, such as project-based learning, problem-based learning and inquiry-based learning, should be employed to foster deep learning and knowledge mastery. (7) Educational policies should encourage innovation and collaboration between educational institutions, government bodies and industry stakeholders to ensure responsiveness to the rapidly evolving landscape of AI in education. (8) Educators should strive to create a learning environment that nurtures and celebrates the unique capabilities of human intelligence while harnessing the power of AI to enhance the learning experience. Social implications (1) Workforce preparedness for an AI-driven future. (2) Potential exacerbation of societal inequalities. (3) Fostering human–AI collaboration skills. (4) Addressing ethical concerns regarding data privacy and security. (5) Emphasizing lifelong learning to adapt to changing demands. (6) Redefining success through a holistic view of student abilities. (7) Shaping societal values that balance human intelligence and AI capabilities. The education system must address these implications to ensure equitable access to AI-enhanced learning, maintain public trust and prepare individuals for a society where human–AI collaboration is essential, while promoting a balanced and harmonious coexistence between human intelligence and AI. Originality/value The article “Nurturing Human Intelligence in the Age of AI: Rethinking Education for the Future” offers a fresh perspective on the impact of AI on education. While the topic of AI in education is not novel, the article’s emphasis on nurturing human intelligence alongside AI integration sets it apart. The author’s call for a fundamental shift in education systems to prioritise critical thinking, creativity and problem-solving skills is a unique approach. The article’s exploration of Learning Mastery and Knowledge Mastery as key concepts in preparing students for an AI-driven future adds originality to the discussion. Overall, the article presents a thought-provoking and original viewpoint on the future of education in the age of AI.